A Rapid Method for Simultaneous Analysis of Lignan and γ‐Tocopherol in Sesame Oil by Using Normal‐Phase Liquid Chromatography. (4th February 2018) - Shi, Long‐Kai; Zheng, Li; Xiang, Yin‐Feng; Liu, Rui‐Jie; Chang, Ming; Jin, Qing‐Zhe; Wang, Xing‐Guo
Abstract: A novel method for rapid and simultaneous analysis of three lignans and γ‐tocopherol in sesame oil has been established based on a one‐step solvent extraction followed by normal‐phase liquid chromatography. The briefness of the experimental procedure, use of 5 mL of n ‐hexane/isopropanol (98:2, v/v) for extraction without any further cleanup process, short analysis time (10 min), and excellent sensitivity and selectivity demonstrated the advantages of this practical and efficient method. All the analytes exhibited satisfactory recoveries ranging from 95.4 to 103.4% at three spiked levels, with the relative SD ranging from 1.1 to 4.4%. The limits of quantitation of this method for four analytes were in the range of 0.3–1.0 μg g −1 . The validated method was successfully applied to the coinstantaneous determination of lignan and γ‐tocopherol in five real sesame oil samples. Furthermore, the results of this study were compared with previously reported method and standard method.